ENHANCING STUDENTS’ WRITING ABILITY BY IMPLEMENTING PROBLEM-BASED LEARNING METHOD AT THE ENGLISH DEPARTMENT STUDENTS IN MUHAMMADIYAH UNIVERSITY OF PONOROGO IN ACADEMIC YEAR 2019/2020 - Windi Astuti; Ana Maghfiroh; Risqi Ekanti Ayuningtyas Palupi (EDUPEDIA, 2020)
Writing is an important language skill because it becomes a means of learning, discovering, developing, and perfecting language skills. The researcher using Problem-Based Learning method to enhance students’ writing ability. This research aims to develop the students’ intelligence by learning to solve problems and shapes students’ interaction with the new environment that confronts students to real world problems to begin learning so that the students become critical thinkers. The researcher used a classroom action research design. The subject was the English department students at Muhammadiyah University of Ponorogo in the academic year 2019/2020. The class consists of 16 students. Before implementing, the researcher made a lesson plan, the steps of Problem-Based Learning method, and prepared instruments, questionnaires, observations, field notes, and test will be conducted in the last meeting. The research was conducted in two cycles. Each cycle consisted of two meetings. Based on the result of the observation it showed that the students were more active than the previous meeting, the percentage was 52% in cycle one and 84% in cycle two. The result of the questionnaire score was 84% in cycle one and 96% in cycle two it means the students were more enjoyed, gave a positive response and looked more fun with the implementation of this method. The result of the writing test in cycle one is that 13 students or 81% who got score ≥ B- (2.5), in cycle two was 100% or all students got score ≥ B- (2.5). The result of writing test in cycle two, it showed improvement. The research finding proves that Problem-Based Learning method was successfully improve writing ability. Hopefully, this research can be a reference for the lecturer of writing course to teach and learn writing and for the next researcher for conducting the next research.